Paediatric neurocysticercosis in high income countries. (July 2022) - Babu, Indhumathi; R Howard-Jones, Annaleise; Goetti, Robert; P Menezes, Manoj; Arbuckle, Susan; N Britton, Philip
Abstract: Background: Neurocysticercosis (NCC) is an unusual cause of seizures in high income settings. It typically presents as an afebrile seizure in a previously well child and can occur years after migration or travel. Methods: Children diagnosed with neurocysticercosis from 01 July 2005 to 30 June 2020 were identified from the electronic medical records of a tertiary children's hospital in Australia. Additionally, a 10-year compilation of case reports of paediatric NCC in high income settings was performed by medline search (publication years 2011–2021). Diagnosis and treatment of neurocysticercosis were reviewed with reference to diagnostic criteria of Del Brutto et al., and the 2017 Infectious Diseases Society of America treatment guidelines. Results: Over a fifteen-year period, eight children were diagnosed with NCC at our hospital in Sydney, Australia. Seizures and history of travel to or migration from South Asia were the two most frequently occurring findings. Children diagnosed after 2016 all received antiparasitic therapy. Outcomes were generally favorable, though long-term epilepsy resulted in some cases. Compiled case reports from high income settings revealed migration and travel exposures commensurate with local demographic patterns, and treatment approaches conforming with 2017 Infectious Diseases Society of America guidelines. Conclusions: Clinicians should be aware of NCC as a differential diagnosis in children from endemic areas presenting with unprovoked seizures as misdiagnosis can occur. Expert review of neuroimaging facilitates diagnosis and can avert unnecessary neurosurgery. In Australia, India was a key exposure country for NCC, reflecting its endemic burden of disease and local travel and migration patterns. Highlights: Neurocysticercosis (NCC) is infrequent in high income countries. NCC should be considered as a differential diagnosis in children with first-episode seizure who have migrated or travelled from endemic areas. Epidemiological risk factors for NCC in non-endemic, high income settings reflect local migration and travel patterns from endemic countries. In Australia, having lived in or travelled to India is a key risk factor for NCC.